(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
In today’s globalization process, the problem of computer-aided understanding and processing of natural language has become one of the most important directions in the field of artificial intelligence. Natural Language Processing (NLP) is a field of science focused on automatic analysis and understanding of human speech. It aims to develop technologies that allow machines to effectively understand and respond to human language by intersecting with the disciplines of Informatics and Linguistics. This article discusses syntactic patterns in the Uzbek language and the issues of their analysis and identification using NLP methods.